Analisis Media Pembelajaran Ular Tangga Untuk Meningkatkan Komunikasi Matematis Secara Tulisan Berbantuan Jigsaw - fadliansyah, fauzi (Universitas Lampung, 2023)
Mathematical communication skills are still categorized as not good. Some research results found that students' mathematics learning is still difficult to do mathematical communication. In addition, the low mathematical communication of elementary students is caused by mathematical communication that is not in line between the teacher and students. To develop students' mathematical communication skills models and learning media are needed that can encourage students to communicate mathematically. One model and media salat that can help students' mathematical communication skills is a cooperative learning model of jigsaw type and neo snake and ladder game media.This study aims to (1) find out the effectiveness of the Jigsaw Cooperative Learning model with the assistance of Neo Snake and Ladder Game media on students' mathematical communication skills and (2) find the pattern of mathematical communication skills in terms of self concept in the cooperative learning model Jigsaw type assisted by Neo Snake media and Ladder Game. The research used is a mix method with a concurrent embedded design. The study was conducted on grade IV students at Sukaratu 4 Public Elementary School and Sukaratu 1 Public Elementary School, Pandeglang Banten. The type of research data obtained from the pretest-posttest, questionnaire, observation and interviews. Analysis of the data used in this study were normality test, homogeneity test, independent sample t-test, and gain test.The results of this study indicate that: (1) the cooperative learning model of jigsaw type assisted by neo snake and ladder game media is effective against mathematical communication skills characterized by achieving classical completeness, the average mathematical communication ability of cooperative learning models of jigsaw type assisted by neo snake media and ladder game is better than mathematical communication skills in the classroom by using ordinary learning and increasing the average mathematical communication skills of students in the experimental class is better than the control class (2) Found patterns of mathematical communication abilities that vary in self-concept groups Low, Medium and High.